Differences in carbon stocks along an elevational gradient in tropical mountain forests of Colombia. (19th June 2019) - Phillips, Juan; Ramirez, Sebastian; Wayson, Craig; Duque, Alvaro
Abstract: Tropical mountain forests provide an exceptional opportunity to evaluate the patterns of variation in carbon stocks along elevational gradients that correspond to well‐defined temperature gradients. We predicted that carbon stored in live aboveground biomass, aboveground necromass, and soil components of forests on the eastern flank of the Colombian Andes would change with elevation along this gradient extending from 750 to 2, 800 m above sea level. The rationale was that the corresponding change in temperature (14–26°C) would influence tree growth and decomposition of organic matter. To address this hypothesis, we examined the carbon stored in these three components using data from 20 0.25‐ha plots located along this elevational gradient. The mean total carbon stock found in the study region was 241.3 ± 37.5 Mg C/ha. Aboveground carbon stocks decreased with elevation ( p  = 0.001), as did necromass carbon stocks ( p  = 0.016). Although soil organic carbon stocks did not differ significantly along the gradient ( p  = 0.153), they contributed proportionately more at higher than at lower elevations, counterbalancing the opposite trends in aboveground carbon and necromass carbon stocks. As such, total carbon stocks did not vary significantly along the elevational gradient ( p  = 0.576).